ALASAN KONSUMEN DALAM MENGKONSUMSI (MEMBELI DAN MEMAKAI) SEPEDA SEBAGAI BARANG MEWAH - Gustiawan, Wahyu Dede; Ismail, Taufiq (Jurnal Ilmiah Mahasiswa FEB, 2015)
The aim of this research is to explore digger concerning to the reason of consumer on consuming bicycle as a luxurious product on members at Komunitas Sepeda Kaskus (KOSKAS) in Malang. This research uses Qualitative approach with phenomenology research design in order to explore concerning to the partisipant is experiances and reasons towards as buying and using bicycle as a luxurious product. The data was taken by interviewing in depth of 6 informers who are members of KOSKAS Malang as partisipants. The data analysis is using coding technique in order a make easier on the meaning formulation process of the depth interview result. The result of this research show: the reasons in which being a background of consumers to buying and using bicycle as a lururious product, there are (1) personality (2) the role of reference group (informational, value expressive) (3) quality product (performances, durability, aesthetics, features, conformance of specification) (4) ideals motivations and Self-expression motivations. Keyword : personality, group reference, quality product, motivation, luxury consumption